Negotiation for disputes settlement in construction claim : a case study on Air Lakitan sub-project-stage 1, Indonesia - Rozamurtina, Dewi (2011)
The construction industry has many factors which contribute to disputes. Disputes waste money and also take attention and energy away from the project. Disputes limit and distort communication and destroy relationships. Dispute can also arisen from construction claim. The contractor can be a claimant and submit their claim documents when they feel they are entitled to be paid some additional money in respect of additional costs they incurred. Negotiation process, as one of ADR methods has been used throughout history to settle disputes. Negotiation involves fewer people, takes less times and usually results in strengthened relationships. The people involved in the negotiation maintain control over negotiation process. The objective of this study is to investigate the negotiation process for disputes settlement on the construction claims for the case study, Air Lakitan Irrigation Sub-Project – Stage-1, Indonesia. The methodology of the study is documentary analysis based on the documents of the project with additional analysis of questionnaire results from the Contractor’s perspective. It is found that the negotiation conducted in Air Lakitan Project is an Integrative Negotiation, or winwin approach to negotiation. The stages involved in negotiation process are; the beginning stage to identify and define the problem/issue; the middle stage to conduct meetings, understand the problem/issue fully, and generate alternative solutions; and the end stage to evaluate and select the alternative to be a deal/agreement. The easiest part of negotiation is the end stage and the hardest part is the beginning stage. Five important elements which have been contributed to the successful negotiation are good communication; skill to negotiate; willingness to work with the other party for a proper understanding of a problem and the needs of other party; willingness to bring all concerns out in the open so that the issues can be resolved in the best possible way; and the effort to investigate issues so well with the other to find a solution that would be acceptable to everyone involved.